Banking 101: Mobile‐izing Financial Inclusion in an Emerging India. (27th February 2013) - Kumar, Neha; Mathur, Akhil; Lal, Siddhartha; Pain, Frédérique; Lively, Scott
Abstract The market for mobile financial services in India is growing steadily. With 41 percent of India's adults financially excluded, however, promoting financial literacy requires serious attention. We present Banking 101—a contextually relevant, mobile storytelling tool that, if integrated with mobile financial offerings, can offer a holistic solution to financial exclusion. © 2013 Alcatel‐Lucent.